Re-conceptualizing regional integration in Africa: The European model and Africa's priorities - Dima Noggo Sarbo (University of Oxford, Global Economic Governance Programme (GEG), 2013)
This paper discusses Africa's attempt at integration as a strategy to overcome its economic crisis and facilitate political stability. It looks at previous, failed attempts at African integration and the bodies established to address the problems faced by African states (namely, the Organization of African Unity (OAU), the Economic Community of West African States (ECOWAS), and the East African Community (EAC)). Today, prolonged conflicts and political stresses continue to hamper economic progress and human welfare, and the continent stands at the bottom of all global indicators of development; no African state has been able to achieve the minimum of the Millennium Development Goals. Thus, the European Union has been heralded as the model for African integration. However, this paper seeks to dispute this conception. The author examines the variables that facilitated European integration, and the historical and geopolitical circumstances that made it possible. In doing so, the author highlights the limited applicability of the EU model to Africa, where there is neither the political nor the economic basis for the type of integration being envisaged. Africa's situation and priorities are starkly different to those that preoccupied European leaders in the 1950s. Rather than attempting to replicate the EU model, this paper puts forward a number of realistic suggestions and alternatives that would begin to address the challenges facing the continent. Among these include: the design and implementation of a regional safety and security regime; the widening of regional markets to promote economic growth; regulatory frameworks in areas related to business; and the management of regional commons, notably shared natural resources.
Keywords: 330